Experience-dependent influence of music and language on lexical pitch learning is not additive - Maggu, Akshay Raj (2021)
Research studies provide evidence for the facilitative effects of musical and linguistic experience on lexical pitch learning. However, the effect of interaction of linguistic and musical pitch experience on lexical pitch processing is a matter of ongoing research. In the current study, we sought to examine the effect of combination of musical and linguistic pitch experience on learning of novel lexical pitch. Using a 10- session pseudoword-picture association training paradigm, we compared the learning performance of musicians and nonmusicians who either spoke a non-tone language, spoke one tone language, or spoke two tone languages. Among the nontone language speakers, we found that musicians showed enhanced learning of novel lexical pitch as compared to nonmusicians. In comparison, among the tone-language speakers, we found no significant difference in the learning performance of musicians and non-musicians no matter they spoke one or more tone languages. We conclude that though musical experience facilitates linguistic pitch learning, the effects of combination of musical and linguistic pitch experience are not additive i.e. possessing both types of pitch experience is no better than possessing either one of them and knowing two tone languages does not facilitate the learning of a new tone language beyond the knowledge of one.